A Study of Collaborative Innovation Mechanism of Prefabricated Construction Enterprises Using Order Parameter - Guo, Zhenxu; Li, Lihong (Frontiers in Built Environment, 2022)
In innovation-driven development, collaborative innovation is gradually becoming a critical sustainable way for prefabricated construction enterprises (PCEs). However, academia and industry do not have a deep understanding of the collaborative innovation of prefabricated construction enterprises (CIPCE), and there is a lack of quantitative-driven research. This study aims to analyze the composition of the CIPCE and measure the operation process and results of the mechanism based on the order parameter. First of all, this study uses semi-structured interviews to analyze the mechanism of CIPCE in the current construction environment. Next, combining structured interviews and literature analysis, the original data was obtained through a questionnaire survey from 15 PCEs in Shenyang, China. Finally, according to the order parameter method, the operation process and results of the CIPCE mechanism are further measured, that is, the synergy and innovation performance that affects its decision-making. The results show that the CIPCE includes four sub-mechanisms: dual drive, resource supply, collaborative operation, and trust guarantee. The orderliness of enterprises has risen overall with partial fluctuations, and the synergy is low. Enterprise innovation performance generally presents a relatively high, but local fluctuations lead to continuous changes. These findings point out the direction for PCEs to maintain their competitiveness in response to the climate crisis and provide action guidelines for the future construction industry to minimize the negative impact on the environment.